2a2+3a+2 |
a+1 |
a2?a?5 |
a+2 |
3a2?4a?5 |
a?2 |
2a2?8a+5 |
a?3 |
=(2a+1)+
1 |
a+1 |
1 |
a+2 |
1 |
a?2 |
1 |
a?3 |
=[(2a+1)-(a-3)-(3a+2)+(2a-2)]+(
1 |
a+1 |
1 |
a+2 |
1 |
a?2 |
1 |
a?3 |
=
1 |
a+1 |
1 |
a+2 |
1 |
a?2 |
1 |
a?3 |
=
1 |
(a+1)(a+2) |
1 |
(a?2)(a?3) |
=
?8a+4 |
(a+1)(a+2)(a?2)(a?3) |
2a2+3a+2 |
a+1 |
a2?a?5 |
a+2 |
3a2?4a?5 |
a?2 |
2a2?8a+5 |
a?3 |
2a2+3a+2 |
a+1 |
a2?a?5 |
a+2 |
3a2?4a?5 |
a?2 |
2a2?8a+5 |
a?3 |
1 |
a+1 |
1 |
a+2 |
1 |
a?2 |
1 |
a?3 |
1 |
a+1 |
1 |
a+2 |
1 |
a?2 |
1 |
a?3 |
1 |
a+1 |
1 |
a+2 |
1 |
a?2 |
1 |
a?3 |
1 |
(a+1)(a+2) |
1 |
(a?2)(a?3) |
?8a+4 |
(a+1)(a+2)(a?2)(a?3) |